Acute Pancreatitis Following the Third Dose of the BNT162b2 COVID-19 Vaccine - Fakhreddine, Omar; Chaabo, Omar; Sharara, Alaa; Arnaout, Mohammad Samir (Archives of Clinical and Medical Case Reports, 2022)
In December 2020, BNT162b2 vaccine developed by Pfizer and BioNTech became the first mRNA-based vaccine approved for human use against COVID-19. The emergence of such techniques in vaccine development have raised concerns about possible side effects. We present the case of a 64-year-old male who presented with acute onset of severe diffuse abdominal pain few days after receiving the third dose of Pfizer BioNTech COVID-19 vaccine. He was diagnosed with acute pancreatitis based on his lipase level of 1483 U/L as well as radiological evidence of pancreatic inflammation. Investigations were unable to detect any evident etiology. He was admitted for observation and conservative management for 24 hours, after which he was discharged home. Few cases of bouts of acute pancreatitis have been reported after the first and second dose of BNT162b2 vaccine. To our knowledge this is the first case of acute pancreatitis after the third dose of vaccine.